Trained Lifeguards Performing Pediatric Cardiopulmonary Resuscitation While Running: A Pilot Simulation Study - Myriam Santos-Folgar; Antonio Rodriguez-Nunez; Roberto Barcala-Furelos; Martín Otero-Agra; Santiago Martínez-Isasi; Felipe Fernández-Méndez (MDPI AG, 2023)
The aim of this study was to compare the quality of standard infant CPR with CPR in motion (i.e., walking and running) via performing maneuvers and evacuating the infant from a beach. Thirteen trained lifeguards participated in a randomized crossover study. Each rescuer individually performed three tests of 2 min each. Five rescue breaths and cycles of 30 chest compressions followed by two breaths were performed. Mouth-to-mouth-and-nose ventilation was carried out, and chest compressions were performed using the two-fingers technique. The manikin was carried on the rescuer's forearm with the head in the distal position. The analysis variables included compression, ventilation, and CPR quality variables, as well as physiological and effort parameters. Significantly lower compression quality values were obtained in running CPR versus standard CPR (53% ± 14% versus 63% ± 15%; p = 0.045). No significant differences were observed in ventilation or CPR quality. In conclusion, lifeguards in good physical condition can perform simulated infant CPR of a similar quality to that of CPR carried out on a victim who is lying down in a fixed position.